How agents change institutions: Coalitional dynamics and the reform of commercial training in Switzerland. (17th December 2018) - Seitzl, Lina; Emmenegger, Patrick
Abstract: Historical institutionalist research has long struggled to come to terms with agency. Yet injecting agency into historical-institutionalist accounts is no easy task. If institutions are structuring agents' actions, while they are simultaneously being structured by these very agents' behavior, the ontological status of institutions remains unclear. Hence, most historical-institutional accounts, at the conceptual level, tend to downplay the role of agency. However, in this way, they also remain incomplete. Following the "coalitional turn" in historical institutionalism, we develop a new account of institutional change and stability that awards a central role to agency. At the heart of our approach is the notion that both stability and change in institutions presuppose constant coalition building by organized entrepreneurial actors. However, for several reasons, such coalition building is complicated, which ultimately leads to institutional stability. In addition, we argue that relevant state agencies actively shape whether the incumbent coalition or the challenger coalition prevails. We illustrate the potential of our actor-centered approach to institutional change by analyzing the reform of commercial training in Switzerland, tracing developments from the beginning of the 1980s until today.